2015
DOI: 10.1103/physrevb.91.205420
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic thermal switch for heat management at the nanoscale

Abstract: In a multi-terminal setup, when time-reversal symmetry is broken by a magnetic field, the heat flows can be managed by designing a device with programmable Boolean behavior. We show that such a device can be used to implement operations, such as on/off switching, reversal, selected splitting and swap of the heat currents. For each feature, the switching from one working condition to the other is obtained by inverting the magnetic field. This offers interesting opportunities for conceiving a programmable setup,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Nowadays the idea of exploiting multiterminal thermoelectric setups is driving the field through a new season of very intense activity . In contrast with conventional two-terminal thermoelectrics, multiterminal thermoelectrics aims at studying a conductor connected, in addition to the two reservoirs at its ends, to (at least) one other reservoir, be it a mere probe [4][5][6][7][8]21], a normal electronic reservoir [9][10][11], a superconducting lead [11][12][13][14], or a reservoir of fermionic [15][16][17]21,22] or bosonic [23][24][25][26][27][28][29][30][31][32][33][34]36] nature that can only exchange energy with the system. Investigations carried out so far have shown that the multiterminal geometry has generally a positive impact on the performance of the thermoelectric devices [7,9,13,21,30], compared to their two-terminal counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays the idea of exploiting multiterminal thermoelectric setups is driving the field through a new season of very intense activity . In contrast with conventional two-terminal thermoelectrics, multiterminal thermoelectrics aims at studying a conductor connected, in addition to the two reservoirs at its ends, to (at least) one other reservoir, be it a mere probe [4][5][6][7][8]21], a normal electronic reservoir [9][10][11], a superconducting lead [11][12][13][14], or a reservoir of fermionic [15][16][17]21,22] or bosonic [23][24][25][26][27][28][29][30][31][32][33][34]36] nature that can only exchange energy with the system. Investigations carried out so far have shown that the multiterminal geometry has generally a positive impact on the performance of the thermoelectric devices [7,9,13,21,30], compared to their two-terminal counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations carried out so far have shown that the multiterminal geometry has generally a positive impact on the performance of the thermoelectric devices [7,9,13,21,30], compared to their two-terminal counterparts. It also opens up new perspectives, such as the possibility of implementing a magnetic thermal switch [10] or of separating and controlling heat and charge flows independently [13].…”
Section: Introductionmentioning
confidence: 99%
“…Co 3 V 2 O 8 has a crystal lattice with space group Cmca. 2,3 The edge sharing CoO 6 octahedra form a staircase kagomé structure and the kagomé staircase lattices are separated by the nonmagnetic VO 4 tetrahedra (see Fig. S1 of the Supplementary Material 15 ).…”
mentioning
confidence: 99%
“…The presence of two different Co 2+ sites along with competing interactions such as the single-ion anisotropy, the nearest-neighbor and the next nearest-neighbor exchanges, and Dzyaloshinskii-Moriya (DM) interactions lead to fascinating magnetic behaviors at low temperatures. [1][2][3][16][17][18][19][20]22,23 In zero field, there are successive magnetic transitions from the paramagnetic (PM) to incommensurate antiferromagnetic (ICAF), commensurate antiferromagnetic (CAF) and commensurate ferromagnetic phases (CF). 1,19 The geometric frustration results in an antiferromagnetic order of Co 2+ spins at a rather low temperature of T N = 11.4 K. 2,16,18 At T N , only the Co 2+ spins locating in the spine site order antiferromagnetically along the a axis.…”
mentioning
confidence: 99%
See 1 more Smart Citation